Special Issue "Drug Discovery of Antiprotozoal Agents" - Francisco Jaime Bezerra Mendonça-Junior (MDPI AG, 2024)
Protozoal diseases, such as leishmaniasis, malaria, African sleeping sickness, Chagas disease, amoebiasis, giardiasis, cryptococcosis, and toxoplasmosis (among others), affect and/or have the potential to infect more than one billion people worldwide [...]